Nonlinear Pulse-Time Conversion in Radioisotope Devices: Analysis and Application Possibilities - A. M. Vodovozov (Приборы и методы измерений)
The paper considers the operation of radioisotope measuring devices under dynamic conditions, when the Poisson pulse flux at the output of the radiation detector becomes unsteady and the nonlinearity of the calibration curve of the device, the stochasticity of the radiation signal and the inertia of the meter significantly complicate the task of estimating the measured physical parameter. of the device and analysis of the possibility of its application for linearization of the characteristics of the device, increasing the speed of the devices and solving the measuring problem in real time.The process of nonlinear transformation of the radiation signal in the system is analyzed on the basis of the assumption about the exponential distribution of the intervals between the pulses of the information flow at the output of the radiation detector. A generalized algorithm for the synthesis of a given transformation function of a time-pulse computing device of a radioisotope device has been developed according to its mathematical description. To describe the transformation function given by a set of points, it is proposed to use its approximation by a power series.The proposed calculation formulas are verified by modeling in the Scilab program on a specific example of linearization of the curve of a radioisotope altimeter with a given tabular calibration characteristic. The results obtained confirm the expediency of using time-pulse computing devices for linearizing the conversion curve of radioisotope devices in real time.Carrying out calculations according to the proposed algorithms by means of modern microelectronics opens up new possibilities for expanding the field of application of radioisotope devices in dynamic problems of industrial flaw detection, measuring the parameters of object movement, thickness of rolled products and coatings, in devices for continuous monitoring of liquid media.